Advanced robotic vehicles programming : an ardupilot and pixhawk approach (Apress, 2020)
Learn how to program robotic vehicles with ardupilot libraries and pixhawk autopilot, both of which are open source technologies with a global scope. This book is focused on quadcopters but the knowledge is easily extendable to three-dimensional vehicles such as drones, submarines, and rovers. Pixhawk and the ardupilot libraries have grown dramatically in popularity due to the fact that the hardware and software offer a real-time task scheduler, huge data processing capabilities, interconnectivity, low power consumption, and a global developer support. This book shows you how take your robotic programming skills to the next level. From hardware to software, Advanced Robotic Vehicles Programming links theory with practice in the development of unmanned vehicles. By the end of this book, you'll learn the pixhawk software and ardupilot libraries to develop your own autonomous vehicles.